Examining the relationships between blubber steroid hormones and persistent organic pollutants in common bottlenose dolphins. (June 2019) - Galligan, Thomas M.; Balmer, Brian C.; Schwacke, Lori H.; Bolton, Jennie L.; Quigley, Brian M.; Rosel, Patricia E.; Ylitalo, Gina M.; Boggs, Ashley S.P.
Abstract: Odontocete cetaceans bioaccumulate high concentrations of endocrine disrupting persistent organic pollutants (POPs), including dichlorodiphenyltrichloroethane (DDT), dichlorodiphenyltrichloroethylene (DDE), and dichlorodiphenyldichloroethane (DDD) – collectively DDTs – but few studies have explored DDTs-mediated endocrine disruption in cetaceans. Herein, we use remotely collected blubber biopsies from common bottlenose dolphins ( Tursiops truncatus ) inhabiting a site with high localized DDTs contamination to study the relationships between DDTs exposure and steroid hormone homeostasis in cetaceans. We quantified blubber steroid hormone concentrations by liquid chromatography-tandem mass spectrometry and blubber POP concentrations by gas chromatography-mass spectrometry. We detected six steroid hormones in blubber, including progesterone (P4 ), 17-hydroxyprogesterone (17OHP4 ), androstenedione (AE), testosterone (T), cortisol (F), and cortisone (E). Sampled dolphins (n = 62) exhibited exposure to DDT, DDE, DDD, chlordanes (CHLDs), mirex, dieldrin, hexachlorobenzene, polychlorinated biphenyls (PCBs), and brominated diphenyl ethers (BDEs). Using principal components analysis (PCA), we determined that blubber DDTs primarily loaded to the first principal component (PC1) explaining 81.6% of the total variance in POP exposure, while the remaining POPs primarily loaded to the PC2 (10.4% of variance). PC1 scores were negatively correlated with blubber T in males and blubber F in females, suggesting that exposure to DDTs impacted androgen and corticosteroid homeostasis. These conclusions were further supported by observed negative correlations between T and o, p'- DDE, o, p'- DDD, and p, p' -DDD in males sampled in the fall, and between F and the six individual DDTs and ∑6 DDTs in females. Overall, these results suggest that POP-mediated endocrine disruption may have occurred in this stock of dolphins, which could negatively impact their health and fitness. However, this study relied on uncontrolled incidental exposures, making it impossible to establish a causal relationship between DDTs exposure and endocrine effects. Importantly, this study demonstrates that remotely collected blubber biopsies are a useful matrix for studying endocrine disruption in marine mammals. Graphical abstract: Image 1 Highlights: First study of DDTs-mediated endocrine disruption in common bottlenose dolphins Organochlorine pesticide exposure linked to disrupted testosterone and cortisol homeostasis Remote blubber biopsies are useful for studying marine mammal endocrine disruption Abstract : Bottlenose dolphins in Florida, USA continue to be exposed to the banned pesticide DDT and may be exhibiting impaired endocrine (hormone) health as a result.